Publons Peer Review Award 2018 for placing in the top 1% of reviewers - Koutinas, Michalis (My University, 2026)
Publons Peer Review Award 2018 for placing in the top 1% of reviewers in the global reviewer database during the 2017-2018 award year.
Keywords: Natural sciences